Stress hyperglycemia, Diabetes mellitus and COVID-19 infection: The impact on newly diagnosed type 1 diabetes - Farakla, Ioanna; Lagousi, Theano; Miligkos, Michael; Nicolaides, Nicolas C.; Vasilakis, Ioannis-Anargyros; Mpinou, Maria; Dolianiti, Maria; Katechaki, Elina; Taliou, Anilia; Spoulou, Vasiliki; Kanaka-Gantenbein, Christina (Frontiers in Clinical Diabetes and Healthcare, 2022)
Several recent studies have documented an increased incidence of newly diagnosed type 1 Diabetes (T1D) cases in children and adolescents during the COVID-19 pandemic and a more severe presentation at diabetes onset. In this descriptive study, we present the experience of the Diabetes Centre of the Division of Endocrinology, Diabetes, and Metabolism of the First Department of Pediatrics of the National and Kapodistrian University of Athens Medical School at “Aghia Sophia” Children’s Hospital in Athens, Greece, concerning new cases of T1D diagnosis during the COVID-19 pandemic (March 2020- December 2021). Patients who had already been diagnosed with T1D and needed hospitalization due to poor control during the pandemic have been excluded from this study. Eighty- three children and adolescents with a mean age of 8,5 ± 4.02 years were admitted to the hospital due to newly diagnosed T1D during this 22 months’ period in comparison to 34 new cases in the previous year. All patients admitted during the pandemic with a new diagnosis of T1D, presented in their majority with DKA (Ph: 7.2) representing an increase of new severe cases in comparison to previous years (Ph 7.2 versus 7.3, p value: 0.021, in the previous year), [p-value: 0.027]. 49 cases presented with DKA, of which 24 were characterized moderate and 14 severe DKA (28.9% and 16,9%, respectively), while 5 patients newly diagnosed, needed to be admitted to the ICU to recover from severe acidosis. Whether a previous COVID- 19 infection could have been the triggering factor is not supported by the SARS-Cov2 specific antibodies analysis in our cohort of patients. As far as HbA1c is concerned there was no statistically significant difference between the pre COVID-19 year and the years of the pandemic (11.6% versus 11.9%, p- value: 0.461). Triglycerides values were significantly higher in patients with new onset T1D during COVID-19 years compared to those before the pandemic (p value= 0.032). Additionally, there is a statistically significant correlation between Ph and Triglycerides for the whole period 2020-2021 (p-value<0.001), while this correlation is not significant for the year 2019. More large- scale studies are required to confirm these observations.